Why Constitutional Courts Back Death Penalty? Insights from Indonesia and South Korea - Omara, Andy; Rahman, Faiz (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
This article explores the paradoxical affirmation of the death penalty by the Constitutional Courts in Indonesia and South Korea, despite constitutional guarantees for the right to life and the fundamental right of human dignity. Through historical and content analyses, it explores how these courts interpret these rights in relation to the death penalty and why they affirm it constitutional. Both countries recognise the nonderogable nature of these rights, yet their Constitutional Courts allow for legal restrictions. Constitutional Court’s decision to impose limitations on nonderogable rights demonstrates their preference for maintaining a cautious and conservative approach. The examination of Constitutional Courts’ decisions reveals that the debate over the death penalty’s constitutionality extends beyond legal considerations, involving political dynamics and historical factors. This article underscores the complex interplay between constitutional guarantees, judicial interpretation, and sociopolitical contexts in shaping the countries’ human rights protection trajectories, especially in the context of nonderogable rights. It also highlights the crucial role of Constitutional Courts in safeguarding the right to life, as their decisions can significantly impact human rights protection in these countries.